Ecologia e comportamento de formigas tecelãs (Camponotus) no Cerrado brasileiro - Santos, Jean Carlos (2002)
The form of nests construction in eusocial insects reveals important steps of its evolutionary history. The weaver ants nests are built starting from the silk that is produced by their own larvas. This form of nests construction is one of the most remarkable instances of social cooperation in animals. The nests construction behavior in the weavers limited to three groups, Oecophylla, Polyrhachis and Camponotus (Karavaievia), of the paleotropical and Australian areas and two of the neotropical area, Dendromyrmex and Camponotus (Myrmobrachys). The behavior and the structure of the weaver C. senex nests and C. formiciformis are little known. These species have been studied by us in the savanna area of the Triângulo Mineiro, in the Univ. Fed. de Uberlândia, and the results reveal that C. senex and C. formiciformis build their nests in trees of dense cup, with many branches and leaves, usually, in the external parts of the cups. The nests are rounds, they present several galleries built around of branches and leaves, they are polygyny and they have between 30.000 and 60.000 individuals. The reproduction begins with the beginning of the rainy station, September to October. They are daytime and feeds small arthropods and animal secretions and vegetables. C. senex possesses proximal defensive mechanisms as release of jets formic acid, the use of the jaws and distant as the sound production similar to the of nests of wasps Polibinae. C. formiciformis presented a complex behavioral repertoire with more than 50 behavior actions, being the first etogram accomplished for a weaver species. The studies of these weaver ants species contribute to a better understanding of the social behavior in animals.